Law and development in East and Southeast Asia - Antons, Christoph (RoutledgeCurzon : IIAS, 2003)
An examination of prospects for commercial law reform in Asia, considering Japan and Singapore as role models for Asian developmentalism, and development related business laws in China, Korea, Indonesia, Malaysia, Vietnam and the Philippines.
Keywords: Law -- Economic aspects -- East Asia.; Law -- Economic aspects -- Southeast Asia.; Law and economic development.; LAW -- Administrative Law & Regulatory Practice.; Law -- Economic aspects.; East Asia.; Southeast Asia.; Rechtshervorming.; Ontwikkelingsproblematiek.; Rechtsstaat.; Economische ontwikkeling.; Electronic books.